2010
DOI: 10.1016/s0167-2991(10)75043-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the carbon nanotube basicity in Pd/N-CNT catalysts on the synthesis of R-1-phenyl ethyl acetate

Abstract: Catalytic activities of palladium catalysts supported on activated carbon and carbon nanotubes were investigated in the one-pot synthesis of R-1-phenylethyl acetate in combination with an immobilized lipase in toluene. Palladium catalysts on carbon nanotubes with nitrogen-containing surface groups were prepared by incipient wetness impregnation. The basic N-CNT support was synthesized by post-treating oxidized CNTs in gaseous NH3 at high temperature, prior to Pd addition. The basic character of the support was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Sahin et al [476] prepared NCNT/Pd catalysts using the incipient wetness impregnation technique. Noble metalcoated NCNTs were also produced on oxidized silicon substrates using catalytic CVD from an aerosol containing droplets of a solution of ferrocene and an acetylacetonate salt of a noble metal (Pt, Ru or Pd) in CH 3 CN [477].…”
Section: Preparation Of Metal/ncnts Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sahin et al [476] prepared NCNT/Pd catalysts using the incipient wetness impregnation technique. Noble metalcoated NCNTs were also produced on oxidized silicon substrates using catalytic CVD from an aerosol containing droplets of a solution of ferrocene and an acetylacetonate salt of a noble metal (Pt, Ru or Pd) in CH 3 CN [477].…”
Section: Preparation Of Metal/ncnts Compositesmentioning
confidence: 99%
“…N-doping was confirmed to lead to the improved selectivity towards the C=C bond hydrogenation and high stability of the catalysts. Moreover, Pd/NCNTs catalyst was used for the synthesis of R-1-phenyl ethyl acetate [476], while Pd/NCNFs was used for (Z)-selective partial hydrogenation of internal alkynes [581]. Chen et al [283] showed that Pd NPs supported on NCNTs show narrower size distribution, compared to the ones deposited over O-functionalized CNTs.…”
Section: Catalysis By 1-d Ncnss and Their Compositesmentioning
confidence: 99%
“…The maximum yield of (R)-1-phenylethyl acetate over Entry 2.0 was 35% at 98% conversion of acetophenone corresponding to 36% selectivity over 312.5 mg of Pd-catalyst in combination with 62.5 mg of immobilized lipase. The desired product yield was improved by using Pd-N-VGCF catalysts comparing to the yields obtained with Pd on active carbon as the maximal yield reported for the latter catalyst was 15% at 66% conversion of acetophenone [35]. In addition for one pot reaction with Pd on ac-tive carbon the major product was ethyl benzene due to the acidic character of the support.…”
Section: Effect Of Ammonia Treatment Temperature On Conversions and Pmentioning
confidence: 98%